Date: Wed, 10 Sep 1997 15:48:04 -0600 (CST)
Subject: Math

Name: Eric
Level: Secondary

Question:

1. 5(-4)-[3(-6)+(-3)-4(2(-4)-7)]+3(-8)=

2. -2[-7-3(4)+5-2(-1)]+3(-6+8)=

3. 4[-6(-2-7)-5(7+2)]=

4. -7(-4)-2[-3(-4+6)+6(7-3(-4))]
P.S. Thank you very much.
Hi Eric,

To do this type of problem you need to start with the quantity that is most deeply embeded in the barckets and work your way out.

1. In the first problem the most deeply embeded quantity is -4, it is contained in three levels of brackets.

5(-4)-[3(-6)+(-3)-4(2(-4)-7)]+3(-8).

2(-4)=-8 and -8-7=-15 so

5(-4)-[3(-6)+(-3)-4(2(-4)-7)]+3(-8)=

5(-4)-[3(-6)+(-3)-4(-15)]+3(-8).

Now the -6, -3 and -15 are contained in two levels of brackets, and evaluating at this level I get

5(-4)-[3(-6)+(-3)-4(-15)]+3(-8)=

5(-4)-[-18-3+60]+3(-8)=

5(-4)-+3(-8).

All the remaining brackets are only one level deep so we can simplify to get

5(-4)-+3(-8)=

-20-39-24=

-83.

2. Applying the samp principle in the second problem I get

-2[-7-3(4)+5-2(-1)]+3(-6+8)=

-2[-7-12+5+2]+3(-6+8)=

-2[-12]+3(2)=

24+6=

30

Cheers,

Harley

Go to Math Central